2019
DOI: 10.3389/fpsyg.2019.01955
|View full text |Cite
|
Sign up to set email alerts
|

The Musical Emotion Discrimination Task: A New Measure for Assessing the Ability to Discriminate Emotions in Music

Abstract: Previous research has shown that levels of musical training and emotional engagement with music are associated with an individual’s ability to decode the intended emotional expression from a music performance. The present study aimed to assess traits and abilities that might influence emotion recognition, and to create a new test of emotion discrimination ability. The first experiment investigated musical features that influenced the difficulty of the stimulus items (length, type of melody, instrument, target-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The same participants also completed a task that required them to compare the emotional features of pairs of musical excerpts (MacGregor & Müllensiefen, 2019), and a series of questionnaires that indexed emotion- and health-related variables. These results will be reported in a separate publication.…”
Section: Methodsmentioning
confidence: 99%
“…The same participants also completed a task that required them to compare the emotional features of pairs of musical excerpts (MacGregor & Müllensiefen, 2019), and a series of questionnaires that indexed emotion- and health-related variables. These results will be reported in a separate publication.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding that the dimensional approach, whether it is formed of two or three variables, generates relevant data, recent studies have confirmed the convenience of discrete emotion recognition for empirical studies. MacGregor and Müllensiefen (2019) verified the consistency of the use of a list of discrete emotions in music and the validation in which music communicates basic emotions. However, the classical discrete point of view, which considers that all sets of emotions can be derived from certain core emotions (Ekman, 1992), has proven insufficient in the case of music-elicited emotions (Scherer and Zentner, 2001; Scherer, 2004; Zentner et al ., 2008).…”
Section: Models Trends and Definitions In The Evaluation Of Music Eventsmentioning
confidence: 74%
“…Richins (1997) proposed the Consumption Emotion Set (CES) with a list of 11 emotions describing the consumer experience. These emotions as defined by Richins consist of “directly experienced emotions that result from the consumption of products.” These perspectives were considering emotions in a generalist way and were applied in multiple contexts, for instance, the features being looked at to analyze the consumer or touristic experience (Richins, 1997), the different manifestations of personality (Fossum and Barrett, 2000) and the assessment of monkey behavior (Martau et al ., 1985). Wood and Moss (2015) and Wood (2015) applied the Richins scale and presented a conceptual model of emotions measured before, during and after a live music event.…”
Section: Models Trends and Definitions In The Evaluation Of Music Eventsmentioning
confidence: 99%
“…Emotion Discrimination Test (EDT) is an adaptive test and uses a two-alternative forced choice (2-AFC) format: two played or sung fragments of the same melody are presented for each task ( MacGregor and Müllensiefen, 2019 ). The participant’s task is to identify which of the two fragments corresponds to the expression of a specific emotion (anger, happiness, sadness, and tenderness).…”
Section: Methodsmentioning
confidence: 99%